Dialogue Concerning Life: Abiogenesis, Biogenesis Or Creationism: Religious Response - Ottuh, Peter O. O. (PREDESTINASI, 2020)
Life itself is a mystery, the how and when of life’s origin constitute a serious challenge to both religion and science. To the reasoning mind, the origination of life is an intellectual problem that needs intellectual resolution especially in the domains of science and religion.  To this extent, some scientific assumptions and postulations concerning the origin of life and the universe are found in a number of theories such as evolution, biogenesis, and abiogenesis among others. Obviously, all these theories pose serious challenges to most religious beliefs including the notion of creationism. In this paper, the historical and critical analytic methods were used to document and evaluate the various religious responses on the subject. The paper posits that religious adherents should acquit themselves with authentic religious beliefs and integrate them with authentic scientific knowledge.